2019
DOI: 10.3390/nano9081148
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid-Polymer Nanoparticle Hybrid Systems as New Tools to Deliver Poorly Soluble Drugs

Abstract: The use of functional excipients such as ionic liquids (ILs) and the encapsulation of drugs into nanocarriers are useful strategies to overcome poor drug solubility. The aim of this work was to evaluate the potential of IL-polymer nanoparticle hybrid systems as tools to deliver poorly soluble drugs. These systems were obtained using a methodology previously developed by our group and improved herein to produce IL-polymer nanoparticle hybrid systems. Two different choline-based ILs and poly (lactic-co-glycolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 76 publications
(164 reference statements)
2
38
0
Order By: Relevance
“…Finally, it was also assessed the release of the rutin from the freshly prepared IL-nanoparticle hybrid systems. An initial burst was observed, as expected, probably due to the rutin adsorbed in the surface of the nanoparticles [35,45]. Nonetheless, this burst release of about 45% happened only after 5 h, probably due to a higher affinity of rutin to the IL-nanoparticles hybrid system, followed by sustained release up to 72 h. This release profile is important to enhance the therapeutic effect and reduce the number of administrations required.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Finally, it was also assessed the release of the rutin from the freshly prepared IL-nanoparticle hybrid systems. An initial burst was observed, as expected, probably due to the rutin adsorbed in the surface of the nanoparticles [35,45]. Nonetheless, this burst release of about 45% happened only after 5 h, probably due to a higher affinity of rutin to the IL-nanoparticles hybrid system, followed by sustained release up to 72 h. This release profile is important to enhance the therapeutic effect and reduce the number of administrations required.…”
Section: Discussionsupporting
confidence: 64%
“…Rutin was loaded in each hybrid system at the maximum solubility of this drug in the presence of either IL, namely, 2.49 mg/mL (4100 µM) with 0. Additionally, the [Cho][Phe]-nanoparticle hybrid system demonstrated that an enhancement of 0.1% of the incorporated IL did not interfere with the hybrid nanosystems stability, but allowed a higher incorporation of the drug and a 10% increase in the AE when compared with the previous prepared hybrid IL-nanocarrier [35]. This shows that the amount of IL impacts drug loading and AE.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The authors suggested that the choline-based ILs could be used as functional ingredients in drug delivery systems suitable for enhancing solubility of other hydrophilic drugs. The use of ILs as functional excipients to overcome poor drug solubility has been proposed recently by Júlio et al [ 217 ]. The authors proposed efficient, non-toxic IL-polymer nanoparticle hybrid systems composed of choline-based ILs and poly (lactic-co-glycolic acid) [PLGA] 50:50 or 75:25 to load rutin into the delivery system.…”
Section: Usefulness Of Ionic Liquids In Medicinementioning
confidence: 99%